The impact of corporate sustainable management activities on customer satisfaction and loyalty in the port industry : an empirical study on Singapore Jurong Port - Sun, Shengmei (2015)
As it is an increasing trend for port operators to engage in initiatives to achieve Corporate Sustainability (CSu), the impact of these activities on port users’ Customer Satisfaction (CS), Customer Loyalty (CL) is worthwhile studying to provide port operators with some managerial implications for better business strategies. Incomprehensive concept definition and limited studies in the multi-purpose port sector bring a sense of urgency to conduct a new research for the benefit of the multi-purpose port operators. This research defines all the activities initiated by business entities to achieve CSu as Corporate Sustainable Management Activities (CSMA), including three pillars - Economically Sustainable Activities (EC), Socially Responsible Activities (SO) and Environmentally Friendly Activities (EN). To address the issue mentioned above, the research was conducted choosing Jurong Port as a case study. Extensive literature review and in-depth interview with Jurong Port managers were firstly carried out to establish the conceptual framework. After that, surveying Jurong Port users’ feedback on Jurong Port’s CSMA, CS and CL was conducted as the major method for data collection. Descriptive Analysis together with Linear Regression Analysis were adopted as methodology for data analysis. Lastly, the result of multi-purpose port sector was compared with container port sector to draw a more comprehensive conclusion. The research result showed there is a positive correlation between “CSMA and CS” and “CSMA and CL”. For the sample data, the impact is mainly contributed positively by SO and EN. The degree of CSMA impact on CL is larger than that on CS probably due to the mediation effect of CS and Corporate Reputation (CR), but the overall impact is limited. Port users’ perception of CSMA is related to their demographic characteristics. Large and mature companies care more about SO and EN and have higher CS and CL. EC is the most known pillar and perceived of the highest value by most port users. Implications are that firstly engagement and publication of each pillar of CSMA shall be conducted considering port user’s awareness and perceived value of these activities. Secondly, port operators should balance the investment in CSMA considering limited degree of impact on CS and CL. Separate service packages shall be provided to small and new port users to maintain market share, as their CS and CL are relatively lower.